Mentoring Of Children With Special Needs Models Sosisc (Soft Skill For Self Confidence) Through Hydroponic Vegetable Cultivation Business - Wasis Suprapto; Slamat Fitriyadi; Dodik Kariadi (STKIP Singkawang, 2022)
Vegetable cultivation can be carried out on limited land by applying the concept of hydroponics. Hydroponic farming can be done by anyone, including children with special needs (ABK) who have been underestimated by most of the community. The purpose of this mentoring activity is to provide skills and foster student self-confidence with a sausage or (soft skill for self confidence) model. The mentoring efforts are carried out using the SPP method, namely socialization, training, and mentoring). The partners of this activity are SLB Negeri and SLB-B Dharma Miranti in Singkawang City The results of the assistance in hydroponic vegetable cultivation business in ABK students using the sausage model led to two findings. First, abk students turned out to have the skills to do vegetable cultivation hydroponically. This can be seen from the ability of ABK students to know and use the equipment and equipment needed to grow crops hydroponically. In addition, they also understand the procedure or stages of growing vegetables hydroponically. Second, mentoring activities that involve the roles of various parties, namely STKIP Singkawang, teachers, and the Singkawang City Agriculture and Forestry Service are able to provide stimulus to foster the confidence of abk students in partner schools